Membangun Center of Excellent Bidang Administrasi Negara Melalui Perpustakaan PKPP A I LAN - Wuri Indri Pramesti; Rina Christina (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2010)
In order to create a competent and professional public servant, it took some effort to give them all updated information that could support decision making process. PKP2A I LAN’s Library has so many role changes in the last few years, in accordance with LAN’s core business, library is directed to become Center of Excellence in Public Administration. This article tries to measure the readiness, changes and improvement that should be done by library. At the end there are some stragies such as building institutional repository, cooperating in ejournal acscess consortium an document delivery service that should be consider as a tools to support center of excellent